Sustainable Digital Business Model Innovation through Learning Factory and AI - Azizah, Nur; Supriati, Ruli; Padeli, Padeli; Mulyati, Mulyati; Apriani, Desy; Fae, Nahlie (Technomedia Journal, 2025)
The digital era compels organizations to continuously innovate in creating sustainable digital business models that integrate technology, human resources, and environmental sustainability. Within this transformation, the Learning Factory emerges as an innovative concept that connects theoretical learning with practical application, enabling students and industry practitioners to co-create solutions through real-world, technology-based projects. Simultaneously, Artificial Intelligence (AI) enhances analytical, predictive, and adaptive capabilities, driving efficiency, innovation, and data-driven decision-making across organizational processes. This study aims to explore the synergy between LearningFactory and AI as a strategic driver of innovation in competitive and sustainable digital business models aligned with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure). Through a qualitative methodology combining literature review and case study analysis of technology-based organizations and higher education institutions implementing the Learning Factory framework, the research identifies how AI integration strengthens learning outcomes, accelerates digital transformation, and promotes sustainability-driven innovation. The findings reveal that this synergy fostersadaptability, enhances human resource competencies, and generates economic,social, and environmental value. Furthermore, it encourages universities and industries to co-develop agile ecosystems that nurture startupreneurship, continuous learning, and inclusive innovation. Ultimately, this study provides strategic recommendations for designing adaptive, competitive, and sustainable digital business models that empower human potential while advancing organizational resilience in the era of rapid technological disruption.